The Effect Of Islamic Leverage On Shariah Compliant Firms’ Performance: Empirical Evidence From Bursa Malaysia - Abdullah Mohammed Ahmed Ayedh; Osman Sayid Hassan Musse; Fauzias Mat Nor (Academia Industry Networks (002911676-U), 2024)
Capital structure is a major corporate finance area which has attracted considerable attention in the recent past with an extensive literature of both theoretical and empirical studies. However, the specific area of Islamic capital structure is relatively underresearched. This paper examines the effects of Islamic leverage on the performance of the continuously- listed shariah-compliant firms on the Main Market of Bursa Malaysia over the period of 2010 to 2017. The paper adopts two major accounting performance measures, i.e., return on equity and return on assets as dependent variables. It employs Islamic leverage containing both total Islamic debt and total interest-bearing debt, which falls within the range of zero to 33% of firm’s total assets as primary criteria for shariah-compliant firms. With a sample size of 305 continuously-listed shariahcompliant firms, which is the whole population that met the sampling requirements, the OLS findings indicate that Islamic leverage has negative and significant effects on shariah-compliant firms’ performance measured by return on assets, while it negatively and insignificantly related to return on equity as performance indicator. The findings also suggest that current ratio, asset turnover and firm size have positive and significant effects on the performance of shariah-compliant firms under both performance measures. The reported descriptive analysis indicates that the average Islamic leverage accounted for 15.7% of firms’ total financing, implying that equity financing represents 84.3% of total financing. The findings suggest that the shariah-compliant firms are largely dependent on internal financing, i.e., retained earnings and equity as a source of funding. Therefore, the findings are in line with Pecking Order Theory suggestions.